High infield performance and critical temperatures in post-annealed MgB2 films. (2nd August 2018) - Horii, Shigeru; Ichinose, Ataru; Iwanaka, Takumu; Kusunoki, Toshiaki; Doi, Toshiya
Abstract: Critical temperatures ( T c ) comparable to those of bulk materials were achieved by post-annealing MgB2 thin films grown at a low temperature of 280 °C. The T c was improved to 36.7 K under annealing conditions of 550 °C for 50 h or more. Under these annealing conditions, a critical current density several tens of times higher at than that of MgB2 wires processed by a powder-in-tube method was achieved at 20 K under 5 T. This is the highest value reported in MgB2 bulk wires and films. Film-based MgB2 is a promising candidate for next-generation MgB2 wires.